A structural equation model of conflict-affected youth coping and resilience. Issue 1 (1st January 2016) - Cherewick, Megan; Tol, Wietse; Burnham, Gilbert; Doocy, Shannon; Glass, Nancy
ABSTRACT: This study tested a theoretical relationship between trauma exposure, youth coping strategies and peer, family and community level factors on psychological distress and well-being among 399 trauma-affected youth in the Democratic Republic of Congo. Structural equation modeling (SEM) was used to analyze paths and to assess differences in relationships by gender. Psychological distress was measured by self-reports of internalizing problems (depression and anxiety), externalizing problems (aggression and behavioral problems) and somatic complaints (pain without medical cause). Self-reports of happiness, hope and self-esteem were measures of well-being. Findings from this study suggest gender differences in how individual coping strategies and external factors explain mental health resilience in trauma-affected youth. Problem-focused coping strategies were associated with higher psychological distress in both boys and girls. Use of avoidance was associated with better well-being in girls and boys and use of faith-based coping strategies was associated with better well-being in boys. Use of both problem-focused and emotion-focused coping strategies (coping flexibility) resulted in lower psychological distress in boys and girls. The home environment including closeness to family, caregiver post traumatic stress disorder and violence in the home was associated with psychological distress and well-being. Having close peer relationships, village safety and enrollment in school benefited well-being. Results from these SEM of resilience suggest that interventions should (1) work to build the coping repertoire of youth, (2) support reduction in psychological distress through improved family relationships and caregiver mental health and (3) target improved well-being through support of positive peer and community relationships and school enrollment.